Fetal Dorsalis Pedis Artery Velocimetry in the Second and Third Trimesters. (1st July 2013) - Zhao, Yili; Zhang, Ming; Zhou, Qichang; Tang, Kui; Wang, Linling; Gong, Zheli
Abstract : Objectives: This study aimed to establish reference ranges for Doppler parameters of the fetal dorsalis pedis artery and to compare them with those of the anterior tibial artery. Methods: Dorsalis pedis artery velocimetry was performed in 138 singleton fetuses. Intraobserver repeatability coefficients and differences between measurements of bilateral legs were also evaluated. Comparisons were made between the pulsatility index in the dorsalis pedis and anterior tibial arteries. Results: The average maximum velocity of the dorsalis pedis artery increased from approximately 12.2 cm/s at 18 weeks' gestation to 33.6 cm/s at 39 weeks' gestation, whereas the minimum velocity did not show any significant variation during the observed gestational weeks. The average pulsatility index increased from about 2.0 at 18 weeks' gestation to 3.1 at 39 weeks' gestation. The pulsatility index was lower in the dorsalis pedis artery than in the anterior tibial artery. Conclusions: Doppler parameters of the dorsalis pedis artery can be easily and accurately acquired by trained examiners and therefore are potential means for evaluating related fetal vascular development. However, it is still unclear whether changes exist in fetuses with limb diseases, and further investigation is needed.